Flotillin-2 expression in the human gut: from a cell model to human tissue in health and inflammatory bowel diseases - Gauss, Annika; Buchholz, Inga; Zahn, Alexandra; Schmitz, Gerd; Stremmel, Wolfgang; Füllekrug, Joachim; Ehehalt, Robert (International journal of medical sciences, 2013)
Background and aims: The etiopathogenesis of inflammatory bowel diseases (IBD) remains largely unexplained. Flotillins (flotillin-1 and flotillin-2) are ubiquitous proteins which have been linked to inflammation and regeneration. We hypothesized that alterations in the expression of flotillin-2 in enterocytes may be related to the pathogenesis of IBD as a classical example of an inflammatory disorder of mostly unknown origin. - Methods: Cell and tissue localization of flotillin-2 (and -1) were investigated by immunofluorescent staining in 1. polarized and unpolarized CaCo-2w cells as a model of human enterocytes (native and after TNFα stimulation) and 2. intestinal biopsies from controls, patients with ulcerative colitis (UC) and patients with Crohn’s disease (CD). For quantification of flotillin-2, we analyzed its expression in ileal and colonic biopsies from controls, UC patients and CD patients using real-time RT-PCR, Western blot and indirect immunofluorescence. - Results: In polarized CaCo-2w cells and human enterocytes in biopsies, flotillins were localized at the basolateral membrane and on subapical vesicles, but not in the apical membrane. Flotillin-2 expression did not differ between UC patients, CD patients and controls. However, it was significantly higher in colonic biopsies compared to ileal biopsies in all groups. - Conclusions: By virtue of its abundant expression in enterocytes, flotillin-2 must have an essential function in intestinal physiology, especially in the colon. Yet our data could not link flotillin-2 to the pathogenesis of IBD.